2018
DOI: 10.1101/253435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilizing ExAC to Assess the Hidden Contribution of Variants of Unknown Significance to Sanfilippo Type B Incidence

Abstract: Given the large and expanding quantity of publicly available sequencing data, it should be possible to extract incidence information for monogenic diseases from allele frequencies, provided one knows which mutations are causal. We tested this idea on a rare, monogenic, lysosomal storage disorder, Sanfilippo Type B (Mucopolysaccharidosis type IIIB).Sanfilippo Type B is caused by mutations in the gene encoding α-N-acetylglucosaminidase (NAGLU). There were 189 NAGLU missense variants found in the ExAC dataset tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…We used 0.15 f wt activity as a threshold with which we distinguished pathogenic from benign variables. This level of f wt activity is consistent with what we observed from previously identified pathogenic mutations as described in Clark et al (). We also calculated AUC and F ‐max values for thresholds ranging from 0.05 to 0.95 in increments of 0.05 (Table S2, Table S3).…”
Section: Methodssupporting
confidence: 93%
See 4 more Smart Citations
“…We used 0.15 f wt activity as a threshold with which we distinguished pathogenic from benign variables. This level of f wt activity is consistent with what we observed from previously identified pathogenic mutations as described in Clark et al (). We also calculated AUC and F ‐max values for thresholds ranging from 0.05 to 0.95 in increments of 0.05 (Table S2, Table S3).…”
Section: Methodssupporting
confidence: 93%
“…Our current in vitro enzyme activity assay is limited to testing missense coding variants, and as shown by Clark et al (), there is a very good agreement with observed activity and pathogenicity of known and well‐annotated disease variants. However, the in vitro assay may not always correlate with enzyme activities tested directly from patient samples.…”
Section: Conclusion and Discussionsupporting
confidence: 62%
See 3 more Smart Citations